Implementation of Problem-Based Learning to Improve Mathematical Critical Thinking Ability of High School Students - Maya Kasmita; Namira Ummi Khalsum (Science Journal Get Press, 2025)
Problem-based learning (PBL) has been recognized as an effective method in improving students' critical thinking skills, especially in mathematics learning. This study aims to analyze the implementation of PBL in improving mathematical critical thinking skills of high school students. The research method used was quasi-experiment with post-test only control group design. The research sample consisted of two randomly selected XI classes, with one class as an experimental group that received PBL learning and one class as a control group with conventional learning methods. The results showed that there was a significant difference between the two groups. The average post-test score of the experimental group was higher than that of the control group, with greater improvement in the interpretation and inference indicators. Statistical tests showed that the application of PBL had a significant positive impact on students' mathematical critical thinking skills. The implications of this study indicate that PBL can be used as an alternative learning strategy that is more effective in improving critical thinking skills in mathematics. Therefore, it is expected that teachers can adopt and develop PBL in learning so that students are more active and independent in solving mathematical problems. Further research is recommended to examine other factors that influence the effectiveness of PBL in improving critical thinking skills.